2021
DOI: 10.1186/s12913-021-07085-w
|View full text |Cite
|
Sign up to set email alerts
|

Patient-public engagement strategies for health system improvement in sub-Saharan Africa: a systematic scoping review

Abstract: Background Actively involving patients and communities in health decisions can improve both peoples’ health and the health system. One key strategy is Patient-Public Engagement (PPE). This scoping review aims to identify and describe PPE research in Sub-Saharan Africa; systematically map research to theories of PPE; and identify knowledge gaps to inform future research and PPE development. Methods The review followed guidelines for conducting and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…The rural community's acceptance of the screening project was satisfactory, with 100% households' participation, highlighting the importance of preliminary health information and community engagement in screening programs. 17 Water and sanitation conditions in the Fanhe area were poor, as well as electricity support, similarly to other parts of the country. 18 Moreover, rate of illiteracy was high, with low basic health knowledge and a high proportion of adults who spoke only local languages.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The rural community's acceptance of the screening project was satisfactory, with 100% households' participation, highlighting the importance of preliminary health information and community engagement in screening programs. 17 Water and sanitation conditions in the Fanhe area were poor, as well as electricity support, similarly to other parts of the country. 18 Moreover, rate of illiteracy was high, with low basic health knowledge and a high proportion of adults who spoke only local languages.…”
Section: Discussionmentioning
confidence: 97%
“…Dedicated staff training was possible in a short period of time and a brief supervision of 15 days allowed correct interpretation of POC test results in all cases but two, indicating that with long‐distance supervision, results could even be improved. The rural community's acceptance of the screening project was satisfactory, with 100% households’ participation, highlighting the importance of preliminary health information and community engagement in screening programs 17 …”
Section: Discussionmentioning
confidence: 99%
“… 22 A more recent review describing patient–public engagement (PPE) strategies for strengthening health systems in SSA found that tokenism rather than actual participation is the main characteristic of PPE in SSA. 23 Their research focused on PPE and its ability to strengthen health systems. Our review goes beyond PPE to evaluate diverse CE in community-based participatory research out of clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…This finding aligns with several recent systematic reviews on community participation. 4,14,[30][31][32] A 2015 research synthesis reported that 95% of initiatives they reviewed engaged communities in implementing interventions, and only 18% involved them in identifying and defining problems. 4 A 2020 systematic review on community participation in humanitarian settings reported limited evidence on involvement of communities in framing issues or designing solutions.…”
Section: Discussionmentioning
confidence: 99%
“…None of the studies reported shared leadership and concluded that the patient public strategies are characterized by tokenism rather than participation. 30 Another systematic review found that communities did not identify health problem research at the problem definition stage but rather learned about a health problem pre-determined by researchers, which is the same case for the BHI. 32 Designers focused the issue on access to primary healthcare services.…”
Section: Discussionmentioning
confidence: 99%